2018
DOI: 10.3390/ijms19092687
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits the Progression of Hepatocellular Carcinoma through MicroRNA Let7i-3p Mediated RAF1 Reduction

Abstract: Melatonin is the main pineal hormone that relays light/dark-cycle information to the circadian system. Recent studies have examined the intrinsic antitumor activity of melatonin in various cancers, including hepatocellular carcinoma (HCC), the primary life-threatening malignancy in both sexes in Taiwan. However, the detailed regulatory mechanisms underlying melatonin’s anti-HCC activity remain incompletely understood. Here, we investigated the mechanisms by which the anti-HCC activity of melatonin is regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Additionally, not only lncRNAs but also some micro-RNAs have been implicated in the anti-invasive and antimetastatic activities of melatonin in HCC. In the same way, also in HepG2 and HuH7 cell lines, administration of 1 and 2 mM melatonin induced the miRNA let7i-p activation, which in turn downregulated the ras activated factor 1 (RAF-1) proto-oncogene, impaired HCC cell migration [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, not only lncRNAs but also some micro-RNAs have been implicated in the anti-invasive and antimetastatic activities of melatonin in HCC. In the same way, also in HepG2 and HuH7 cell lines, administration of 1 and 2 mM melatonin induced the miRNA let7i-p activation, which in turn downregulated the ras activated factor 1 (RAF-1) proto-oncogene, impaired HCC cell migration [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recent studies have demonstrated that melatonin may also modulate the expression of non-coding microRNAs (or, miRNA), which modulate many aspects of tumor phenotypes in breast, liver and gastric cancers [21,22,23]. In fact, melatonin may modulate expression of specific microRNAs that function across multiple tumor types, such as miR-155, miR-133a and miR-21 [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, let‐7i‐3p was found to be related to hepatocellular carcinoma and hepatoblastoma (HBL). RAF1 reduction mediated by let‐7i‐3p plays a role in melatonin inhibition of hepatocellular carcinoma . Indersie et al reported that let‐71‐3p, miR‐449b‐3p, and miR‐885‐5p were decreased in tumors compared to normal livers, and that these miRNAs inhibited HBL cell grow and Wnt signaling activity in vitro, partly through beta‐catenin downregulation .…”
Section: Discussionmentioning
confidence: 99%